Struktur Komunitas dan Biomassa Ikan Target pada Terumbu Karang KKLD Misool Selatan, Papua Barat Daya - Frederik Rijoly; Stefanno Markus Anthony Rijoly; Kedswin Gerson Hehanussa (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Coral reef ecosystems are among the most biodiverse marine ecosystems and play a crucial role in supporting tropical fisheries productivity and the sustainability of coastal resources. Monitoring the biomass of target fish is an important indicator for assessing ecosystem condition and the effectiveness of marine protected area management. This study aimed to analyze species richness and the biomass structure of target fish in the Food Security and Tourism Sub-Zone of the Regional Marine Conservation Area (KKLD) of South Misool, Southwest Papua. Data were collected from May 8 to 16, 2025, at 12 sites using the Underwater Visual Census (UVC) method at depths of 5 m and 12 m. The results recorded 80 species belonging to 15 families, with species richness ranging from 22 to 43 species per site. The total biomass of target fish reached 1665.62 tons/km², ranging from 24.97 to 640.03 tons/km², with the highest biomass observed at Magic Mountain and the lowest at Fyabya. Biomass distribution was strongly influenced by the presence of large-bodied and schooling species. Correlation analysis indicated no significant relationship between species richness and fish biomass (p > 0.05), suggesting that biomass is primarily driven by body size and the dominance of particular species rather than species number. Overall, the target fish community in this area is considered to be in good condition and supports sustainable coral reef ecosystem management.